JUMLAH DAN PANJANG ABSOLUT KROMOSOM BAWANG MERAH KULTIVAR SAMAS (ALLIUM ASCALONICUM L. CV. SAMAS) - Dian Ayuning Tyas Dian Ayuning Tyas (AGRONOMIKA, 2014)
Samas red shallot cultivar is originated from Samas, Bantul, Yogyakarta. This red shallot have double gloves, spicy taste and spesific aroma. Thus red shallot cultivar can be also harvested quickly compared to other red shallot cultivars.Genetic characterization of this red shallot cultivar has not been examined yet. Genetic characterization of this red shallot cultivar is very important to be applied for breeding program and ger m plasm conservation. Therefore, the aim of this research were to determine chromosome number and total length of this red shallot cultivar as a preliminary research on chromosome characterization. Method used for chromosome preparation in this research was a squash method. The result showed that time of mitosis occured from . until . am with time of prometafase stage was at . am. The diploid chromosome number (2n) of this red shallot cultivar was 16, and the chromosome total length was between ,6 ± , μm and ,6 ± ,6 µm.